AN ANALYSIS OF ABBREVIATIONS FOUND IN “TORAM ONLINE” - Arief Kurniadi; Saunir Saunir (Universitas Negeri Padang, 2018)
This research focused on types of abbreviations found in”Toram Online”. The aims of this research were (1) to find types of abbreviations, and (2) to identify how the comparisons between each type of abbreviations are. This research is a descriptive research. The results of the analysis of data are presented in the form of description and explanation. Data in this research were 126 special terms used in the interaction between players in game. These data were gained and analyzed by means of observation and interpretation by the researcher. The results of the research show that there were five types of abbreviations. They were 26 clipping(20%), 25 omission(20%), 64 initialism(50%), 5 logogram(5%), 6 nonstandardspelling(5%). The players tend to use abbreviations because there was limitation of characters that can be used in one time chat.